2022
DOI: 10.1016/j.ijfoodmicro.2021.109498
|View full text |Cite
|
Sign up to set email alerts
|

Improved microbial and sensory quality of chicken meat by treatment with lactic acid, organic acid salts and modified atmosphere packaging

Abstract: Microbial contamination and growth play important roles in spoilage and quality loss of raw poultry products. We evaluated the suitability of three commercially available organic acid based antimicrobial compounds, Purac FCC80 (L-lactic acid), Verdad N6 (buffered vinegar fermentate) and Provian K (blend of potassium acetate and diacetate) to prevent growth of the innate microbiota, reduce spoilage and enhance the sensory quality of raw chicken under vacuum, high CO 2 (60/40% CO 2 /N 2 ), and high O 2 (75/25% O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 77 publications
2
8
0
Order By: Relevance
“…So, to an effective cool chain and MAP packaging, further physical or chemical strategies could be tested to improve the food safety, microbial quality, and shelf life of chicken meat (83). However, BAI can be considered as a useful tool to monitoring the effectiveness of technological treatments, being an indirect index of microbial spoilage and directly involved in toxicity events.…”
Section: Discussionmentioning
confidence: 99%
“…So, to an effective cool chain and MAP packaging, further physical or chemical strategies could be tested to improve the food safety, microbial quality, and shelf life of chicken meat (83). However, BAI can be considered as a useful tool to monitoring the effectiveness of technological treatments, being an indirect index of microbial spoilage and directly involved in toxicity events.…”
Section: Discussionmentioning
confidence: 99%
“…Organic acids have mostly been used by the food industry and, therefore, tested against foodborne pathogens during food and feed production [21][22][23][24][25][26][27]. Previous studies on the effects of different doses of organic acids on meat spoilage bacteria [28,29], Clostridium perfringens and C. difficile [30,31], Staphylococcus aureus and Escherichia coli [32], enteropathogenic bacteria [14], demonstrated that they have the potential to act as antimicrobial agents. However, their antibacterial efficacy against enteric pathogens in the environment has not been fully explored, particularly in biological waste treatment plants where VFAs are produced as intermediates of such processes.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional meat processing line usually involves cleaning and disinfection steps to reduce pathogens (Smith et al, 2015) . Some of the most common conventional mild processing technologies used for the decontamination of commercial meat products include physical treatments, i.e., washing Sá Júnior et al (2021), steaming (Dixon et al, 2019), chemical treatments, i.e., organic acids (Heir et al, 2022), chlorinated chemicals (Kocharunchitt et al, 2020), hydrogen peroxide (Walsh et al, 2018), phosphate-based compounds (Sallam L. et al, 2020). Sodium hypochlorite is one of the most used, efficient, available, and low-cost disinfectants.…”
Section: Introductionmentioning
confidence: 99%